The black coral fauna (Cnidaria: Antipatharia) of Bermuda with new records - Wagner, Daniel; Shuler, Andrew (Zootaxa, 2017)
The black coral fauna of Bermudan waters is poorly known, in large part due to the logistical challenges of surveying deep-water (>50 m) environments where most species occur. In 2016, the Nekton Expedition sought to survey the deep-water biodiversity around Bermuda using manned submersibles and mixed-gas technical SCUBA. A total of 28 black coral specimens were collected, and these were examined based on skeletal spine morphology, polyp morphology, colony branching pattern and in situ photographs. The specimens were assigned to seven species in three families and four genera, including (1) Antipathes atlantica Gray, 1857, (2) Antipathes furcata Gray, 1857, (3) Stichopathes pourtalesi Brook, 1889, (4) Stichopathes sp., (5) Distichopathes filix (Pourtales, 1867), (6) Tanacetipathes hirta (Gray, 1857), and (7) Tanacetipathes tanacetum (Pourtales, 1867). Of these, three species (Stichopathes sp., S. pourtalesi, and D. filix), one genus (Distichopathes) and one family (Aphanipathidae) are reported from Bermudan waters for the first time, thereby increasing the known black coral diversity of Bermuda to twelve species, five genera and four families. The diagnostic characters of the taxa identified as part of this study are illustrated and described.